Pengaruh Lingkungan Sosial Sekolah terhadap Perkembangan Sosial Emosional Anak Usia Dini melalui Instrumen Penilaian Skala - Amanda Surya Aisyah; Gita Anastasya Sinaga; Imelda Anisa Vretty Gultom; Leli Abrina Sihombing (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to identify the role of home and preschool environments on the socioemotional development of early childhood. Through an observation and assessment approach using validated instruments, this study found that the social environment, both at home and at school, has a significant influence on the development of children's ability to recognize, express, and manage emotions, as well as build healthy social relationships. The results show that children who receive positive support from their environment tend to have better socioemotional development, characterized by the ability to recognize emotional expressions, apply politeness values, and show good moral behavior. This research emphasizes the importance of the role of family and school in shaping children's character and emotional intelligence from an early age